Effect of different levels of green tea (Camellia sinensis) and mulberry (Morus alba) leaves powder on performance, carcass characteristics, immune response and intestinal morphology of broiler chickens - Fatemeh Aziz‐Aliabadi; Hadi Noruzi; Ahmad Hassanabadi (Veterinary Medicine and Science, 2023)
Abstract Background In recent years, the use of medicinal plants as an alternative to antibiotics has expanded. Plants containing medicines and antioxidants can improve the performance of poultry. Objectives The purpose of this study was to achieve the appropriate levels of green tea leaf powder (GTP) and mulberry leaf powder (MLP) in the diet, which positively affects broilers’ performance. Methods 648 one‐day‐old Ross 308 broiler chickens were allocated to nine dietary treatments with six replicates and each replicate containing 12 birds based on a completely randomised design (CRD) in a factorial arrangement of 3 × 3 with three levels of GTP, and three levels of MLP for 42 days. Treatments included: (1) no GTP + no MLP (control), (2) 1% GTP + no MLP, (3) 2% GTP + no MLP, (4) no GTP + 1% MLP, (5) 1% GTP + 1% MLP, (6) 2% GTP + 1% MLP, (7) no GTP + 2% MLP, (8) 1% GTP + 2% MLP and (9) 2% GTP + 2% MLP. Results The results revealed that the effect of added powders (2%) was significant and increased daily weight gain (DWG) and reduced feed conversion ratio (FCR) compared to the control group during the grower and whole phases (p < 0.05). On 35 days, the control and 2% GTP + 2% MLP treatment had the lowest and highest antibodies titre (total and immunoglobulin G [IgG]), respectively (p < 0.05). The groups fed with 1% GTP + 1% MLP showed higher villus height (VH) compared to the control, 2% GTP + 1% MLP, 1% GTP + 2% MLP, and 2% GTP + 2% MLP groups (p < 0.05). The ratio of the villus height to crypt depth (VH: CD) in treatments 1% GTP + no MLP, 2% GTP + no MLP and 1% GTP + 1% MLP was significantly higher than the control treatment (p < 0.05). Conclusions It was concluded that the addition of 2% GTP or MLP could improve humoral immune response and performance, and the addition of 1% GTP without MLP increased VH: CD in broilers.